2009
DOI: 10.1029/2008jd011263
|View full text |Cite
|
Sign up to set email alerts
|

Significant decadal brightening of downwelling shortwave in the continental United States

Abstract: [1] We conduct analyses of all-sky and clear-sky surface downwelling shortwave radiation and bulk cloud properties using data from several Department of Energy Atmospheric Radiation Measurement (ARM) Program and National Oceanic and Atmospheric Administration Surface Radiation (SURFRAD) network sites spanning the years 1995 through 2007. Five ARM sites are aggregated to study downwelling shortwave tendencies on global circulation model grid scales, and then six SURFRAD sites plus the central ARM site are aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
122
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 59 publications
18
122
0
1
Order By: Relevance
“…The RRTMG_SW results in Bondville show that changing aerosols influences SWdn trends. Taken together, the observations and modeled results suggest that aerosol-radiation interactions are significant at Bondville, a conclusion doubted in previous studies (Long et al, 2009;Augustine and Dutton, 2013). We find evidence that these interactions play a role in the observed climate trends at Bondville, similar in response to modelling studies that probed the influence of aerosols on the warming hole (Leibensperger et al, 2012b).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The RRTMG_SW results in Bondville show that changing aerosols influences SWdn trends. Taken together, the observations and modeled results suggest that aerosol-radiation interactions are significant at Bondville, a conclusion doubted in previous studies (Long et al, 2009;Augustine and Dutton, 2013). We find evidence that these interactions play a role in the observed climate trends at Bondville, similar in response to modelling studies that probed the influence of aerosols on the warming hole (Leibensperger et al, 2012b).…”
Section: Discussionsupporting
confidence: 59%
“…However, the diffuse component of clear-sky SWdn increases at both Bondville (+6.6 Wm −2 ) and Goodwin Creek (+5.2 Wm −2 ), consistent with previous studies (e.g., Gan et al, 2014) and the cause of these increases remains an open question. We do not find evidence of aircraft contrails influencing observed diffuse SWdn at SURFRAD sites in the aftermath of 11 September 2001, and thus caution against attributing increasing clear-sky diffuse SWdn trends to increasing US air traffic as has been done in previous studies (e.g., Long et al, 2009;Augustine and Dutton, 2013).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Aerosol loading over North America was relatively light (35) and rather stable during the past few decades (8). Observations at six stations in the United States showed that R s significantly increased from 1995 to 2007 (36,37), primarily in the 1990s (38).…”
Section: Significancementioning
confidence: 99%